Synthesis and characterization of new inhibitors of cholinesterases based on N-phenylcarbamates: In vitro study of inhibitory effect, type of inhibition, lipophilicity and molecular docking - Vorčáková, Katarína; Májeková, Magdaléna; Horáková, Eva; Drabina, Pavel; Sedlák, Miloš; Štěpánková, Šárka (Bioorganic chemistry, 2018)
Based on current treatment of Alzheimer's disease, where the carbamate inhibitor Rivastigmine is used, two series of carbamate derivatives were prepared: (i) N-phenylcarbamates with additional carbamate group (1-12) and (ii) N-phenylcarbamates with monosaccharide moiety (13-24). All compounds were tested for the inhibitory effect on both of the cholinesterases, electric eel acetylcholinesterase (eeAChE) and butyrylcholinesterase from equine serum (eqBChE) and the inhibitory activity (expressed as IC50 values) was compared with that of the established drugs Galanthamine and Rivastigmine. The compounds with two carbamate groups 1-12 revealed higher inhibitory efficiency on both cholinesterases in compared with monosaccharide derived carbamates 13-24 and with Rivastigmine. The significant decrease of inhibitory efficiency on eqBChE (also for eeAChE but in less manner) was observed after deacetalization of monosaccharide. Moreover, the type of inhibitory mechanism of five chosen compounds was studied. It was found, that compounds with two carbamate groups act presumably via a mixed inhibitory mechanism and the compounds with monosaccharide moiety act as non-competitive inhibitors. The lipophilicity of tested compounds was determined using partition coefficient. Specific positions of the inhibitors in the binding sites of cholinesterases were determined using molecular modeling and the results indicate the importance of phenylcarbamate orientation in the catalytic gorges of both enzymes.
Keywords: Animals; Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; vztah mezi dávkou a účinkem léčiva; Electrophorus; Molecular Structure; fenylkarbamáty; Structure-Activity Relationship; koně; Horses; Ligands; Models, Molecular; Phenylcarbamates; molekulární struktura; Dose-Response Relationship, Drug; molekulární modely; acetylcholinesterasa; hydrofobní a hydrofilní interakce; vztahy mezi strukturou a aktivitou; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; ligandy; Hydrophobic and Hydrophilic Interactions